Pengaruh Penerapan Media Kartu Baca terhadap Kemampuan Membaca Permulaan Siswa Kelas 1 SDN - Septiana Fira Mawarni; Titis Angga Rini; Muh Arafik; Septiana Fira Mawarni; Titis Angga Rini (Universitas Negeri Malang, 2022)
Abstract: Beginning reading is an early stage that supports other language skills. Good reading skills can affect student learning success. This research is motivated by the problems that occurred at SDN Cemorokandang 01 Malang City, namely the lack of effective learning due to the pandemic period so that learning has been running for one semester there are still students who still have difficulty in reading the beginning and affect the student learning process, because students read to learn. The purpose of this study was to determine the application and influence of reading card media on the early reading ability of first graders at SDN Cemorokandang 01 Malang City. This study uses a quantitative approach with the Pre-Experimental Design method. The type of design used is One Group Pretest-Posttest Design. The number of samples in this study were 30 students with a total sampling technique. Data collection techniques used are observation, tests, and documentation. The data analysis technique used is the Wilcoxon Signed Rank Test nonparametric statistical test. Observation results show the percentage of 77 percent with the category of students participating in learning using reading card media well. The results of data analysis using the Wilcoxon Signed Rank Test obtained a significance of 0.000 less than 0.05, which means that there is a significant difference between the initial reading ability of first-class students at SDN Cemorokandang 1 Malang before and after learning using reading card media. Abstrak: Membaca permulaan merupakan tahap awal yang mendukung kemampuan berbahasa yang lainnya. Kemampuan membaca yang baik dapat berpengaruh dalam kesuksesan belajar siswa. Penelitian ini dilatarbelakangi oleh masalah yang terjadi di SDN Cemorokandang 01 Kota Malang yaitu kurang efektifnya pembelajaran karena masa pandemi sehingga sudah berjalan pembelajaran selama satu semester masih terdapat siswa yang masih kesulitan dalam membaca permulaan dan mempengaruhi proses belajar siswa, karena siswa membaca untuk belajar. Tujuan dari penelitian ini adalah untuk mengetahui penerapan dan pengaruh media kartu baca terhadap kemampuan membaca permulaan siswa kelas 1 SDN Cemorokandang 01 Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode Pre- Experimental Design. Jenis desain yang digunakan, yaitu One Group Pretest-Posttest Design. Jumlah sampel dalam penelitian ini adalah 30 siswa dengan teknik total sampling. Teknik pengambilan data yang digunakan adalah observasi, tes, dan dokumentasi. Teknik analisis data yang digunakan adalah uji statistika nonparametrik Wilcoxon Signed Rank Test. Hasil observasi menunjukkan persentase 77 persen dengan kategori siswa mengikuti pembelajaran menggunakan media kartu baca dengan baik. Hasil analisis data menggunakan uji Wilcoxon Signed Rank Test diperoleh signifikansi 0,000 kurang dari 0,05 yang artinya terdapat perbedaan yang signifikan antara kemampuan membaca permulaan pada siswa kelas I SDN Cemorokandang 1 Kota Malang sebelum dan sesudah pembelajaran menggunakan media kartu baca.